A planetesimal orbiting within the debris disc around a white dwarf star - Manser, Christopher J.; Quirrenbach, Andreas; Reffert, Sabine (Science, 2019)
A low-mass planet around a white dwarf - Numerous exoplanets have been detected around Sun-like stars. These stars end their lives as white dwarfs, which should inherit any surviving planetary systems. Manser et al. found periodic shifts in emission lines from a disc of gas orbiting around a white dwarf (see the Perspective by Fossati). They used numerical simulations to show that the most likely explanation for the spectral shifts is a low-mass planet orbiting within the disc. The planet must be unusually small and dense to avoid being ripped apart by tidal forces. The authors speculate that it may be the leftover core of a planet whose outer layers have been removed. - Science, this issue p. 66; see also p. 25 - Many white dwarf stars show signs of having accreted smaller bodies, implying that they may host planetary systems. A small number of these systems contain gaseous debris discs, visible through emission lines. We report a stable 123.4-minute periodic variation in the strength and shape of the Ca ii emission line profiles originating from the debris disc around the white dwarf SDSS J122859.93+104032.9. We interpret this short-period signal as the signature of a solid-body planetesimal held together by its internal strength. - A small, dense planet orbits within the gaseous disc around a white dwarf. - A small, dense planet orbits within the gaseous disc around a white dwarf.
Gesehen am 14.05.2019